Large-Area and Patternable Nano-Dot Array from Electrolysis of ITO Film for Surface-Enhanced Raman Spectroscopy - Han Lu; Gengxin Han; Jieping Cao; Mingliang Jin; Qilin Ma; Eser Metin Akinoglu; Xin Wang; Li Nian; Guofu Zhou; Lingling Shui (Nanoscale Research Letters, 2020)
Abstract Fabrication of large-area devices with patternable nanostructures is important for practical applications in optical or electrical devices. In this work, we describe an easy and environment-friendly method for preparing large-area nano-dot (ND) arrays via the electrolytic reaction of a metal oxide film. NDs with various size and morphology can be obtained by adjusting the applied voltage, electrolysis time, and the film thickness of the indium tin oxide (ITO) layer. High-density NDs with size of 50–60 nm can be obtained by electrolysis of a 25-nm-thick ITO film at 150 V for 1.5 min under a water droplet medium, which have been applied for surface-enhanced Raman spectroscopy (SERS) after depositing a thin layer of silver. The SERS substrate with optimized ND structure exhibits sensitive detection of Rhodamine 6G (R6G) with detection limit down to 5 × 10-12 M. The enhancement factors (EFs) of 1.12 × 106 and 6.79 × 105 have been achieved for characterization of 4-methylbenzenethiol (4-MBT) and R6G, respectively. With an additional photolithographic step, multiple areas of ND arrays can be created on one substrate, enabling simultaneous detection of various samples containing different molecules at once experiment. Such a method is quick, easy, patternable, and environment-friendly, being suitable for on-site quick and synchronous determination of various molecules for applications in point-of-care, environmental monitoring, and airport security fields.